Sumatriptan Nasal Spray for Acute Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The efficacy and side effects of intranasal sumatriptan (20 mg, 10 mg) or placebo in the treatment of a single migraine attack were evaluated in two randomized, double-blind, multicenter studies of 409 and 436 adult patients, funded by Glaxo Wellcome.